If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2 = -2y + -7 Reorder the terms: 2 + 3y = -2y + -7 Reorder the terms: 2 + 3y = -7 + -2y Solving 2 + 3y = -7 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 2 + 3y + 2y = -7 + -2y + 2y Combine like terms: 3y + 2y = 5y 2 + 5y = -7 + -2y + 2y Combine like terms: -2y + 2y = 0 2 + 5y = -7 + 0 2 + 5y = -7 Add '-2' to each side of the equation. 2 + -2 + 5y = -7 + -2 Combine like terms: 2 + -2 = 0 0 + 5y = -7 + -2 5y = -7 + -2 Combine like terms: -7 + -2 = -9 5y = -9 Divide each side by '5'. y = -1.8 Simplifying y = -1.8
| 3[x-2]=-9 | | 6x+2x=9x-6 | | 4(-x+3)=36 | | m+40+90=180 | | 21=-8(4n-3)-3 | | 6X-7=5(2X+7) | | 7x+3x-8x-5=9 | | 3(4+6a)+6a=-36+8a | | (-124)-(-254)= | | 14x+10=-7 | | 2x+5x-3x-5=7 | | 3xa=12 | | -8(-8-8x)=-8-8x | | 1-5n=-2(4-2n) | | P^2+16p-33=0 | | 25+(-12)+13(-30)= | | (6c)2= | | 2x=-7-11 | | 21+52a=-7a^2 | | 3(x+4)=-13+8x | | 9x+7y=36 | | 2x=-5x-15 | | f(x)=x^5+3.5x^4-2.5x^3-125x^2+1.5x+9 | | -9=18.9 | | 20=-5(x+1) | | 8+9y=6y-10 | | M*2=144 | | m+54+61=180 | | 7-2(4a-3)=25-5a | | 3a^2=48+18a | | .5y+-.75y=0 | | 2(n^2+5n-104)=0 |